2022
DOI: 10.1155/2022/6839385
|View full text |Cite
|
Sign up to set email alerts
|

AKG Attenuates Cerebral Ischemia-Reperfusion Injury through c-Fos/IL-10/Stat3 Signaling Pathway

Abstract: Inflammation is dominant in the pathogenesis of ischemic stroke (IS). Alpha-ketoglutarate (AKG), according to previous studies, has demonstrated a variety of pharmacological effects such as antioxidation and inhibitive inflammation activities. However, whether AKG ameliorates cerebral ischemic injury, as well as the underlying molecular events, is still unclear. Therefore, the effect and underlying mechanisms of AKG on ischemic brain injury should be identified. The study established a cerebral ischemia-reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…When an excessive accumulation of ROS occurs in the body, it can lead to oxidative damage to sperm, potentially resulting in conditions like oligozoospermia or even azoospermia [30] . Key antioxidants, including SOD and GSH-Px, play essential roles in safeguarding cells against oxidative stress [31] . MDA is a product of lipid peroxidation triggered by ROS, and its content serves as an indicator of the extent of oxidative damage to cell membranes [32] .…”
Section: Oxidative Stress and Endocrine Imbalance As Precursors To MImentioning
confidence: 99%
“…When an excessive accumulation of ROS occurs in the body, it can lead to oxidative damage to sperm, potentially resulting in conditions like oligozoospermia or even azoospermia [30] . Key antioxidants, including SOD and GSH-Px, play essential roles in safeguarding cells against oxidative stress [31] . MDA is a product of lipid peroxidation triggered by ROS, and its content serves as an indicator of the extent of oxidative damage to cell membranes [32] .…”
Section: Oxidative Stress and Endocrine Imbalance As Precursors To MImentioning
confidence: 99%
“…When an excessive accumulation of ROS occurs in the body, it can lead to oxidative damage to sperm, potentially resulting in conditions like oligozoospermia or even azoospermia [ 45 ]. Key antioxidants, including SOD and GSH-Px, play essential roles in safeguarding cells against oxidative stress [ 46 ]. MDA is a product of lipid peroxidation triggered by ROS, and its content serves as an indicator of the extent of oxidative damage to cell membranes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that activation of the STAT3 pathway after cerebral ischemia can change the microglial phenotype from pro-inflammatory to anti-inflammatory, partially improving brain injury [ 44 , 45 ]. Huang et al have demonstrated that the FOS/IL-10/STAT3 pathway can play a neuroprotective role in cerebral ischemia [ 46 ]. Additionally, as previously reported, the activated STAT3/NFIL3 pathway and STAT3–NFkB/DDIT3/CEBPβ axis play regulatory roles in chemotherapy resistance [ 47 , 48 ], and lipopolysaccharide can induce the expression of DUSP1 and regulate macrophages through MAPK-STAT3 axis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%